Distinct expression profile in fumarate-hydratase-deficient uterine fibroids. - Vanharanta, S; Pollard, P; Lehtonen, H; Laiho, P; Sjöberg, J; Leminen, A; Aittomäki, K; Arola, J; Kruhoffer, M; Orntoft, T; Tomlinson, I; Kiuru, M; et al. (2006)
Defects in mitochondrial enzymes predispose to severe developmental defects as well as tumorigenesis. Heterozygous germline mutations in the nuclear gene encoding fumarate hydratase (FH), an enzyme catalyzing the hydration of fumarate in the Krebs tricarboxylic acid cycle, cause hereditary leiomyomatosis and renal cell cancer; yet the connection between disruption of mitochondrial metabolic pathways and neoplasia remains to be discovered. We have used an expression microarray approach for studying differences in global gene expression pattern caused by mutations in FH. Seven uterine fibroids carrying FH mutations were compared with 15 fibroids with wild-type FH. The two groups showed markedly different expression profiles, and multiple differentially expressed genes were detected. The most significant increase in FH mutants was seen in the expression of carbohydrate metabolism- and glycolysis-related genes. Other significantly up-regulated gene categories in FH mutants were, for example, iron ion homeostasis and oxidoreduction. Genes with lower expression in FH-mutant fibroids belonged to groups such as extracellular matrix, cell adhesion, muscle development and cell contraction. We show that FH mutations alter significantly the expression profiles of fibroids, most strikingly increasing the expression of genes involved in glycolysis.